Different Methods of Pretreatment Ki-67 Labeling Index Evaluation in Core Biopsies of Breast Cancer Patients Treated with Neoadjuvant Chemotherapy and Their Relation to Response to Therapy - Vörös András; Csörgő Erika; Kővári Bence; Lázár Péter; Kelemen Gyöngyi; Rusz Orsolya; Nyári Tibor András; Cserni Gábor (2015)
Increased proliferation activity of breast cancer cells evaluated by Ki-67 immunohistochemistry, i.e. a high Ki-67 labeling index (Ki-67 LI), may predict better tumor regression in case of neoadjuvant chemotherapy. Despite recommendations for the evaluation of Ki-67 LI, there are variations in methodology. We assessed the effect of different evaluation methods on the Ki-67 LI in patients with different response to neoadjuvant chemotherapy. Thirty pretreatment core-biopsy samples of patients receiving neoadjuvant docetaxel-epirubicin chemotherapy with or without capecitabine were evaluated for their Ki-67 LI. Pathologic regression was categorized as no regression, partial regression and complete regression, with 10 cases in each category. Three antibodies (MIB1, B56, SP6), 4 observers and 4 methods (counting or estimating on glass slides and counting or estimating on representative digital images) were compared. The Kruskal-Wallis test and analyses of variance were performed to investigate the differences in Ki-67 LIs between different clinical outcomes (tumor regression categories). Breast carcinomas with pathological complete regression had a higher mean Ki-67 LI than tumors not achieving complete regression with any methods, observers and antibodies investigated, although there was a variation between different evaluations in what may represent high proliferation. Estimating the Ki-67 LI on digital images representing the highest proliferation in the core biopsy seemed the best in separating complete responders from non-responders. High Ki-67 LI values were more likely associated with pathological complete regression independently of the method of evaluation used, although the definition of high proliferation is problematic. Estimating the Ki-67 LI may be an adequate method of evaluation.